Integrated procurement-production inventory model in supply chain: A systematic review - Dana Marsetiya Utama; Imam Santoso; Yusuf Hendrawan; Wike Agustin Prima Dania (Operations Research Perspectives, 2022)
Inventory affects the production process and supply chain activities. Integrated decision inventory improves performance and optimizes supply chain activities. However, its disadvantage is the Integrated Procurement Production (IPP) inventory model, which manages the raw material inventory in procurement activities, works in process, and finished products. This study reviewed the IPP inventory model problem using a systematic review of 102 published papers from 1992 to 2021. The reviewed papers were based on complexity, type of model, data, time dynamics, optimization, solution, and paper. This study presented the IPP inventory model analysis, gap, and future study directions.
Keywords: 650; Systematic review; Procurement production; Inventory model; Supply chain